Sticky Exchange Rates and Flexible Prices : A Heretic View From the Interwar Period - Gulde, Anne (IMF Working Papers; Working Paper ;, 1991)
Real exchange rate variability tends to be higher under flexible than under fixed exchange rates. The neokeynesian view attributes the higher variability to the combination of volatile nominal exchange rates with sticky prices. The neoclassical approach regards an increased incidence of real shocks as the culprit. We test the crucial assumptions underlying the two models for the interwar period. Prices and exchange rates are found to be equally flexible. We hence reject the neokeynesian sticky price view for our sample period. In contrast, our results are consistent with, while not constituting evidence for, the neoclassical equilibrium approach.